Bioassessment of environmental quality based on taxonomic and functional traits of marine nematodes in the Bohai Sea, China. (May 2023) - Hua, Er; He, Lei; Zhang, Zhinan; Cui, Chunyan; Liu, Xiaoshou
Abstract: Free-living marine nematodes are valuable biological indicators for different environmental disturbances. Their taxonomic composition and functional traits often respond to environmental changes. In this study, marine nematodes, collected from the Bohai sea on the northeastern coast of China in 2014, were investigated in terms of their taxonomic composition and functional traits. Furthermore, the environmental quality of the investigated area was assessed based on nematode metrics. The studied nematode community showed spatial variation in taxonomic and functional composition, in response to changes in environmental variables such as sediment chlorophyll-a, phaeophytin-a, organic matter content, silt-clay content etc. Overall, high percentage of tolerant marine nematodes species or colonizers predominated, suggesting a disturbed environmental condition of the study area. Further results from the environmental quality assessment based on nematode metrics indicated a moderate quality status at the most investigated stations. Highlights: Nematodes contributed to the indication of certain disturbed habitats. Nematodes reflected the influence of river discharge and land-based pollution. Tolerant species or colonizers predominated the studied nematode communities. Most investigated stations had moderate environmental quality status.